Bee Dance - Chrustowski, Rick (New York : Henry Holt and Company, 2015)
"A honeybee searches for nectar, then returns to the hive to tell the other bees. She does a waggle dance, moving in a special figure-eight pattern to share the location of the foodsource with her hivemates. With vivid and active images, Rick Chrustowski brings these amazing bees to life!"--
Keywords: Honeybee -- Behavior; Juvenile literature; Worker honeybees -- Juvenile literature; Animal communication -- Juvenile literature